Modified matrix-free methods for solving system of nonlinear equations. (2nd November 2021) - Waziri, Mohammed Yusuf; Muhammad, Hadiza Usman; Halilu, Abubakar Sani; Ahmed, Kabiru
Abstract : Some hybrid derivative-free methods for nonlinear system of equations via acceleration and correction parameters are presented. These methods are based on applying the three term hybrid iterative scheme on an enhance matrix free method. The step length was determined using an inexact line search procedure. Moreover, the proposed methods proved to be globally convergent under mild conditions. The comprehensive numerical results presented in this work, show the efficiency of the proposed methods by comparing them with some existing methods in the previous literature.